DARING:PENGEMBANGAN E-BOOKLET DIGITAL PARENTING CARA MENCEGAH KECANDUAN GADGET PADA ANAK USIA DINI - Mayrina Eka P (Jurnal Konseling Pendidikan Islam, 2021)
This research aims to produce a digital parenting e-booklet which discusses ways to prevent gadget addiction in early childhood. This research is a development research (Research and Development) with the ADDIE model. The stages in the study consisted of analysis, design, development, implementation and evaluation.The data collection methods were interview and questionnaire. The data were analyzed using descriptive statistics. The results showed that the digital parenting ebooklet product which discusses ways to prevent gadget addiction was successfully created through the development process (Research and Development) with the ADDIE model. Through the validation process, there were scores of 52 (86.67%) %) from two material experts, 122 ( 90.37%) scores of two media experts, and 44,125 (88.25%) of the eight parents who were used as users. Based on the results of validation of the material, media experts and users in trials can conclude that theparenting digital e-booklet media is appropriate to be used as a medium of information for parents of early childhood.